SHELF-LIFE ESTIMATION OF PINEAPPLE CHIPS BY A WATER SORPTION ISOTHERM CURVE APPROACH - Dewi Fortuna Ayu; Nurmadhona Nurmadhona; Raswen Efendi (AGROINTEK, 2023)
Pineapple chips have low moisture content and water activity, so they are able to absorb water from the environment and have an impact on shorter shelf life.  One way to reduce the absorption of moisture is by choosing to package with good barrier properties. This study conducted experimentally to estimate the shelf life of household products of pineapple chips with aluminum foil and polypropylene packaging using the water sorption isotherm (ISA) curve approach. Some models of the ISA curve equation were tried, including GAB, Hasley, Caurie, Chen Clayton, Oswin, and Henderson. The parameters observed in this study consisted of initial, critical, and equilibrium moisture content, determination of the water sorption isotherm curve, slope value, saturated vapor pressure, packaging permeability, packaging area, dry weight per package, and calculation of shelf life. The results showed that the selected ISA curve equation model for pineapple chips was the Hasley model with the equation Log [In 1/aw)] = Log -1.73 + Log 1.42 Me. Permeability of polypropylene packaging was obtained at 0.1275 (g/m2.hari.mmHg), while aluminum foil was 0.0441 (g/m2.hari.mmHg). Therefore, pineapple chips have a shorter shelf life with polypropylene packaging compared to aluminum foil. The shelf life of pineapple chips with polypropylene packaging at RH 70-90% was 31.5-46.5 days, while aluminum foil packaging at RH 70-90% was 87.3-129.3 days with a critical water content of 0.0674 g H2O/g of the material. The use of aluminum foil packaging extended 2-3 times the shelf life of pineapple chips to increase the added value of the household industry of pineapple chips